Loving my (LGBT) neighbor : being friends in grace & truth - Stanton, Glenn T., 1962- (Chicago : Moody Publishers, 2014)
"To love our neighbor as ourselves is the second great command that our Savior gave us, eclipsing all others, but one. Curiously, the question of "who is my neighbor?" came up the very moment Jesus gave us this command. And it comes up today. Jesus was colorfully clear; our neighbor includes the person who lives on the far end of our ideological or sociological spectrum. In light of and despite the divisive issue that homosexuality has become in both culture and the church, Loving My (LGBT) Neighbor is conceived and thoughtfully written--from the author's decade-plus years of engaging this issue at all levels--for the Christian layperson or clergy who want to learn how to receive and interact with their gay or lesbian neighbors in a substantively Christ-honoring way"--
Foreword -- Preface: The great equalizer -- Introduction: Is this really working for anyone? -- Understanding the thing itself -- Sex : what is it that God says -- The problem of false choices -- Folks who are getting it right -- Navigating the dilemmas we face in our friendships -- Navigating the dilemmas we face in our homes and churches -- Navigating the dilemmas we face in our society -- Conclusion: Why all this matters.
Includes bibliographical references.
Keywords: Homosexuality -- Religious aspects -- Christianity; Sex role -- Religious aspects -- Christianity; Love -- Religious aspects -- Christianity; RELIGION / Christian Life / Social Issues; Homosexuality -- Religious aspects -- Christianity; Love -- Religious aspects -- Christianity; Sex role -- Religious aspects -- Christianity